The Influence of Headmaster's Interpersonal Communication on Teacher's Work Motivation in MTs Al- Jam’iyatul - Hendri Fauza (Education Achievement: Journal of Science and Research, 2023)
The aim of this research is to determine and analyze the influence of headmaster's interpersonal communication on the work motivation of teachers at MTs Al-Jam’iyatul Wasliyah Tembung. This research is descriptive in nature, employing a quantitative approach. The independent variable (X) in this study is the headmaster's interpersonal communication, while the dependent variable (Y) is teacher's work motivation. The population for this study consists of 35 teachers at MTs Al-Jam’iyatul Wasliyah Tembung. The sample size is 35 respondents, selected through total sampling technique. Data collection is done using a questionnaire survey method. Data analysis is performed using SPSS Statistics 25.0, involving descriptive and regression analysis. The research findings indicate a positive and significant influence of the headmaster's interpersonal communication (X) on teacher's work motivation (Y) at MTs Al-Jam’iyatul Wasliyah Tembung. Based on the partial test (T-test), the obtained t-value is 4.518 with a significant value of 0.000, while the critical t-value is 2.035 at a 95% confidence level. Hence, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The assumptions for analysis show that the data is normally distributed, homogenous, and linear. Based on the conducted research, it can be concluded that the variable of Headmaster's Interpersonal Communication significantly impacts the improvement of Teacher's Work Motivation at MTs Al-Jam’iyatul Wasliyah Tembung.